Low-shrinkage holographic polymer dispersed liquid crystal material, grating device and preparation method thereof

By introducing acrylate monomers with different functionalities into the holographic polymer dispersed liquid crystal material, and adjusting their ratio to improve the polymerization reaction efficiency, the problem of high shrinkage of the material during the polymerization and curing process is solved, and high precision of the grating device is achieved. and controllability.

CN118894959BActive Publication Date: 2025-01-17NIKA OPTICS (TIANJIN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411388111.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-17
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing holographic polymer dispersed liquid crystal materials have a high shrinkage rate during polymerization and curing, resulting in grating period distortion and affecting the clarity of the hologram.

Method used

By introducing the first monomer, the second monomer and the third monomer with different functionalities, the ratio is adjusted to improve the conversion efficiency of the monomer polymerization reaction and reduce the shrinkage of the material. Specifically, a monofunctional first monomer, a difunctional second monomer, and a trifunctional third monomer are selected for combination.

Benefits of technology

It effectively reduces the shrinkage rate of the holographic polymer dispersed liquid crystal material during the polymerization and solidification process after interference exposure, improves the precision and controllability of the grating device, while reducing production costs and improving production convenience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_15
    Figure SMS_15
Patent Text Reader

Abstract

The present invention provides a low-shrinkage holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof. Specifically, the low-shrinkage holographic polymer dispersed liquid crystal material comprises a solvent, a liquid crystal, a photoinitiator, a co-initiator, a first monomer, a second monomer and a third monomer; wherein the first monomer is selected from one or more of 4-tert-butylcyclohexyl acrylate, C8-C10 acrylate and lauric acid methacrylate; the second monomer is selected from one or more of tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate and dioxane hexaglycol diacrylate; and the third monomer is 3-ethoxylated trimethylolpropane trimethacrylate. By selecting and combining polymer monomers in the holographic polymer dispersed liquid crystal material, the shrinkage rate of the holographic polymer dispersed liquid crystal material during the polymerization and curing process is reduced, and the precision of the prepared grating device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of holographic projection display, and more specifically, to a low-shrinkage holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof. Background Art

[0002] Nowadays, with the continuous updating and iteration of market demand and technology, various holographic technologies are gradually applied to various occasions in people's lives. Among them, holographic display technology is the most intuitive application of holographic technology. With the continuous development of holographic technology, holographic display technology is also gradually being integrated into various fields such as reflective flat-panel displays, teaching displays, medical diagnosis and treatment, and military technology.

[0003] As one of the fastest-growing, most widely used, and most closely related optoelectronic materials since the last century, liquid crystal is still widely used in the display of various electronic devices. Thanks to the tunable nature of liquid crystal materials, the arrangement direction of liquid crystal molecules can be controlled by applying external fields such as electric fields, magnetic fields, and heat, thereby realizing different functions of the device, greatly improving the multi-dimensional flexible controllability of devices in the current electronics industry. Among them, polymer dispersed liquid crystal (PDLC) is an optoelectronic functional device based on liquid crystal / polymer materials. It mainly transforms the mixture of liquid crystal and prepolymer into liquid crystal droplets dispersed in the polymer substrate by photopolymerization or thermal polymerization to cause phase separation, and then uses the electrical control characteristics of liquid crystal to control the orientation of liquid crystal molecules by applying an external voltage, thereby changing the refractive index of liquid crystal to match or mismatch the refractive index of the polymer, resulting in the polymer dispersed liquid crystal film switching between light transmission or light scattering under the action of an electric field.

[0004] The formation and preparation of holographic polymer dispersed liquid crystal (H-PDLC) gratings are inseparable from the development of holographic technology and polymer dispersed liquid crystals, and are a combination of the two. Among them, holographic polymer dispersed liquid crystal materials are formed by the polymerization of a mixture of nematic liquid crystals, initiators, and monomers in the interference field of two laser beams with high coherence, equal intensity, and the same polarization state. In the bright stripe area of ​​the interference field, the prepolymer monomer undergoes free radical photopolymerization, and at the same time, the concentration of the monomer in this area decreases. The change in concentration gradient causes the monomer at the dark stripe to diffuse toward the bright stripe, and the liquid crystal droplets gather toward the dark stripe. As time goes by, polymer areas and liquid crystal areas corresponding to the bright stripes and dark stripes are gradually formed, forming an H-PDLC grating with periodic arrangement of polymer-rich layers and liquid crystal-rich layers.

[0005] As a composite material, holographic polymer dispersed liquid crystal usually uses acrylic monomers. After acrylic monomers are exposed to an interference light field, they polymerize. The polymerization reaction causes changes in the distance between atoms, and the change in entropy from monomer to polymer causes material shrinkage, which will change the grating period and cause the hologram to show distortion. Therefore, it is urgent to solve the problem of acrylic monomer shrinkage in practical applications. Summary of the invention

[0006] The present invention aims to overcome at least one defect of the above-mentioned prior art and provides a low-shrinkage holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof, thereby reducing the shrinkage rate of the holographic polymer dispersed liquid crystal material during the polymerization and curing process and improving the accuracy of the holographic polymer dispersed liquid crystal grating device.

[0007] The technical solution adopted by the present invention is first to provide a low-shrinkage holographic polymer dispersed liquid crystal material, which comprises, by mass percentage:

[0008] Solvent: 5%-10%,

[0009] LCD: 35-55%,

[0010] Photoinitiator: 0.5-2%,

[0011] Co-initiator: 0.5-10%,

[0012] First monomer: 5-40%,

[0013] Second monomer: 5-40%,

[0014] The third monomer: 1-10%;

[0015] The first monomer, the second monomer and the third monomer are acrylates with different functionalities;

[0016] The first monomer is selected from one or more of 4-tert-butyl cyclohexyl acrylate, C8-C10 acrylate and lauric acid methacrylate;

[0017] The second monomer is selected from one or more of tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate and dioxane hexanedioic acid diacrylate;

[0018] The third monomer is 3-ethoxylated trimethylolpropane trimethacrylate.

[0019] In the present technical solution, by adding a first monomer, a second monomer and a third monomer with different functionalities, the conversion efficiency of the monomer polymerization reaction can be improved by adjusting the ratio of the monomers with different functionalities added, so that the holographic polymer dispersed liquid crystal material is more suitable for exposure processing. Only a small amount of solvent needs to be added for dilution to allow the monomer to move effectively in space, thereby improving the efficiency and function of the prepared holographic grating device. Specifically, the first monomer is a monofunctional monomer selected from one or more of 4-tert-butylcyclohexyl acrylate, C8-C10 acrylate and lauric acid methacrylate; the second monomer is a bifunctional monomer selected from one or more of tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate and dioxane glycol diacrylate; the third monomer is a trifunctional monomer, specifically, 3-ethoxylated trimethylolpropane trimethacrylate; the combination of the three polymer monomers reduces the shrinkage of the holographic polymer dispersed liquid crystal material during the polymerization and curing process after interference exposure, thereby making the directional arrangement and photocuring of the grating period formed when the holographic polymer dispersed liquid crystal material is used to prepare the holographic volume grating device more precise and controllable. Secondly, the shrinkage of the material is reduced by selecting and combining the polymer monomers contained in the holographic polymer dispersed liquid crystal material, and the raw materials are widely available and easy to obtain. While ensuring the function of the holographic volume grating device, the production convenience is improved and the production cost is reduced.

[0020] Furthermore, the photoinitiator is selected from one or more of rose bengal, methylene blue and phenanthrenequinone.

[0021] Furthermore, the co-initiator is selected from one or more of methyldiethanolamine, p-toluenesulfonic acid and N-phenylglycine.

[0022] Furthermore, the liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.

[0023] Furthermore, the solvent is selected from one or more of N,N-dimethylacrylamide, 2-ethylhexyl acrylate, dimethylformamide and N-ethylpyrrolidone.

[0024] Another object of the present invention is to provide a method for preparing a holographic polymer dispersed liquid crystal grating device. The preparation method has a simple process, does not require post-curing, has low production cost, and high production efficiency. The preparation method specifically comprises the following steps:

[0025] The low-shrinkage holographic polymer dispersed liquid crystal material provided in the technical solution is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.

[0026] Optionally, the interference exposure time is 1-5 min, and the irradiation power is 3.5-5.5 mW / cm 2 ; The angle between the dual-beam light sources is 40°-60°.

[0027] Preferably, a double beam angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed to a dual-beam light source for 3 min to prepare a holographic polymer dispersed liquid crystal grating device.

[0028] Optionally, the thickness of the liquid crystal box is 5 μm-10 μm.

[0029] Preferably, the low-shrinkage holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum atmosphere, and allowed to stand in a dark room for 1 hour.

[0030] Another object of the present invention is to provide a holographic polymer dispersed liquid crystal grating device, which is prepared by the preparation method provided by the technical solution.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: first, by introducing three monomers, namely, a first monomer, a second monomer and a third monomer, with different functionalities into a holographic polymer dispersed liquid crystal material, the conversion efficiency of the monomer polymerization reaction can be improved by adjusting the ratio of the monomers with different functionalities added, so that the holographic polymer dispersed liquid crystal material is more suitable for exposure processing, thereby improving the function of the prepared holographic volume grating device. Secondly, specifically, the first monomer is a monofunctional monomer selected from one or more of 4-tert-butylcyclohexyl acrylate, C8-C10 acrylate and lauric acid methacrylate; the second monomer is a bifunctional monomer selected from one or more of tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate and dioxane diol diacrylate; the third monomer is a trifunctional monomer, specifically, 3-ethoxylated trimethylolpropane trimethacrylate; through the combination of the three polymer monomers, the shrinkage rate of the holographic polymer dispersed liquid crystal material in the polymerization and curing process after interference exposure is reduced, so that the directional arrangement and the grating period formed by photocuring when the holographic polymer dispersed liquid crystal material is used to prepare the holographic volume grating device are more precise and controllable. At the same time, the shrinkage of the material is reduced by selecting and combining the polymer monomers contained in the holographic polymer dispersed liquid crystal material, and the source of the raw materials is wide and easy to obtain. While ensuring the function of the holographic volume grating device, the production convenience is improved and the production cost is reduced. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0034] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels).

[0035] Example 1

[0036] This embodiment provides a low-shrinkage holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0037] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0038] Rose Bengal 1.5%, N-phenylglycine 5%, P0616A 35%, 4-tert-butylcyclohexyl acrylate 24%, propoxylated neopentyl glycol diacrylate 22%, 3-ethoxylated trimethylolpropane trimethacrylate 5%, N,N-dimethylacrylamide 3%, N-ethylpyrrolidone 4.5%.

[0039] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0040] The weighed raw materials are mixed evenly to obtain a low-shrinkage holographic polymer dispersed liquid crystal mixed liquid.

[0041] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0042] The low shrinkage holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.

[0043] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0044] (4) Shrinkage test

[0045] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0046] S = ×100%, where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0047] Example 2

[0048] This embodiment provides a low-shrinkage holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0049] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0050] Methylene blue 1.5%, p-toluenesulfonic acid 8%, E7 37%, C8-C10 acrylate 25%, tricyclodecane dimethanol diacrylate 18%, 3-ethoxylated trimethylolpropane trimethacrylate 3%, N,N-dimethylacrylamide 4.5%, dimethylformamide 3%.

[0051] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0052] The weighed raw materials are mixed evenly to obtain a low-shrinkage holographic polymer dispersed liquid crystal mixed liquid.

[0053] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0054] The low shrinkage holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.

[0055] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0056] (4) Shrinkage test

[0057] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0058] S = ×100%,

[0059] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0060] Example 3

[0061] This embodiment provides a low-shrinkage holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0062] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0063] Methylene blue 1%, methyldiethanolamine 6%, E63 38%, lauric acid methacrylate 30%, 13% 1,2-dioxanediol diacrylate, 4% 3-ethoxylated trimethylolpropane trimethacrylate, 3% 2-ethylhexyl acrylate, and 5% dimethylformamide.

[0064] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0065] The weighed raw materials are mixed evenly to obtain a low-shrinkage holographic polymer dispersed liquid crystal mixed liquid.

[0066] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0067] The low shrinkage holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.

[0068] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0069] (4) Shrinkage test

[0070] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0071] S = ×100%,

[0072] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0073] Comparative Example 1

[0074] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0075] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0076] Rose Bengal 1.5%, N-phenylglycine 5%, P0616A 35%, ethoxylated phenoxy acrylate 16%, propoxylated neopentyl glycol diacrylate 17%, 3-ethoxylated trimethylolpropane trimethacrylate 6%, N,N-dimethylacrylamide 3%, N-ethylpyrrolidone 4.5%.

[0077] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0078] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0079] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0080] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0081] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0082] (4) Shrinkage test

[0083] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0084] S = ×100%,

[0085] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0086] Comparative Example 2

[0087] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0088] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0089] Methylene blue 1.5%, p-toluenesulfonic acid 5%, E7 35%, C8-C10 acrylate 16%, 1,4-butanediol dimethacrylate 17%, 3-ethoxylated trimethylolpropane trimethacrylate 6%, N,N-dimethylacrylamide 4.5%, dimethylformamide 3%.

[0090] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0091] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0092] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0093] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0094] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0095] (4) Shrinkage test

[0096] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0097] S = ×100%,

[0098] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0099] Comparative Example 3

[0100] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0101] (1) Weigh the raw materials in the brown sample according to the following mass percentages: methylene blue 1.5%, methyldiethanolamine 5%, E63 35%, ethoxylated phenoxy acrylate 16%, 1,4-butanediol dimethacrylate 17%, 3-ethoxylated trimethylolpropane trimethacrylate 6%, 2-ethylhexyl acrylate 4.5%, and dimethylformamide 15%.

[0102] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0103] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0104] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0105] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0106] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0107] (4) Shrinkage test

[0108] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0109] S = ×100%,

[0110] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0111] Comparative Example 4

[0112] This comparative example provides a holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:

[0113] (1) Weigh the raw materials in the brown sample according to the following mass percentages:

[0114] Rose Red 1%, N-phenylglycine 6%, BL038 40%, C8-C10 acrylate 23%, 1,2-dioxanediol diacrylate 20%, pentaerythritol triacrylate 5%, N,N-dimethylacrylamide 3%, N-ethylpyrrolidone 2%.

[0115] (2) Preparation of holographic polymer dispersed liquid crystal materials:

[0116] The weighed raw materials are mixed evenly to obtain a holographic polymer dispersed liquid crystal mixed liquid.

[0117] (3) Preparation of holographic polymer dispersed liquid crystal grating devices

[0118] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum conditions. The liquid crystal box has a thickness of 5 μm and is left to stand in a dark room for 1 hour.

[0119] Then, a double beam with an angle of 50° and an optical power of 4.5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.

[0120] (4) Shrinkage test

[0121] According to the principle of light interference, the shrinkage rate of holographic polymer dispersed liquid crystal materials is tested by using the Michelson interferometer and the offset of the interference fringe position. During exposure, the slight change in the thickness of the holographic polymer dispersed liquid crystal material during the curing process will affect the optical path difference, causing the light beam to form different interference patterns. Therefore, the offset of the interference fringe position in the interferometer spectrum can be used to accurately calculate the shrinkage rate of the material according to the following formula:

[0122] S = ×100%,

[0123] Where λ is the wavelength of the light source (633nm), N is the number of interference rings in the interference pattern at time t, is the thickness of the material before curing (μm).

[0124] The shrinkage results calculated by using the offset of the interference fringe positions in the interferometer patterns of the seven holographic polymer dispersed liquid crystal materials in Examples 1 to 3 and Comparative Examples 1 to 4 and their exposure and curing are shown in the following table:

[0125]

[0126] By comparing the embodiments and the comparative examples, it can be found that in Embodiments 1 to 3, the first monomer, the second monomer and the third monomer are selected and combined according to the acrylate monomers provided in the present technical solution in the holographic polymer dispersed liquid crystal material, while in Comparative Examples 1 to 4, at least one of the first monomer, the second monomer and the third monomer selected in the holographic polymer dispersed liquid crystal material is combined with other acrylate monomers. The obtained shrinkage test results show that when the first monomer, the second monomer and the third monomer are selected and combined according to the acrylate monomers provided in the present technical solution in the holographic polymer dispersed liquid crystal material, the shrinkage of the holographic polymer dispersed liquid crystal material after exposure and curing can be greatly reduced, thereby greatly improving the precision of the prepared holographic polymer dispersed liquid crystal grating device.

[0127] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A low shrinkage holographic polymer dispersed liquid crystal material, characterized in that: In terms of mass percentage, it includes: Solvent: 5%-15%, LCD: 35-55%, Photoinitiator: 0.5-2%, Co-initiator: 0.5-10%, First monomer: 5-40%, Second monomer: 5-40%, The third monomer: 1-10%; The first monomer is selected from one or more of 4-tert-butyl cyclohexyl acrylate, C8-C10 acrylate and lauric acid methacrylate; The second monomer is selected from one or more of tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate and dioxane hexanedioic acid diacrylate; The third monomer is 3-ethoxylated trimethylolpropane trimethacrylate.

2. The low shrinkage holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The photoinitiator is selected from one or more of rose bengal, methylene blue and phenanthrenequinone.

3. The low shrinkage holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The co-initiator is selected from one or more of methyldiethanolamine, p-toluenesulfonic acid and N-phenylglycine.

4. The low shrinkage holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.

5. The low shrinkage holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The solvent is selected from one or more of N,N-dimethylacrylamide, 2-ethylhexyl acrylate, dimethylformamide and N-ethylpyrrolidone.

6. A method for preparing a holographic polymer dispersed liquid crystal grating device, characterized in that: The following steps are involved: The low-shrinkage holographic polymer dispersed liquid crystal material according to any one of claims 1 to 5 is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.

7. The preparation method according to claim 6, characterized in that: The interference exposure time is 1-5 minutes, and the irradiation power is 3.5-5.5 mW / cm 2 ; and the angle between the dual-beam light sources is 40°-60°.

8. The preparation method according to claim 6, characterized in that: The thickness of the liquid crystal cell is 5-10 μm.

9. The preparation method according to claim 6, characterized in that: The low shrinkage holographic polymer dispersed liquid crystal material is mixed and filled into a liquid crystal box under a vacuum atmosphere, and allowed to stand in a dark room for 1 hour.

10. A holographic polymer dispersed liquid crystal grating device, characterized in that: Prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Polymer dispersed liquid crystal material and manufacturing method thereof

    CN109423299A

  • Holographic photopolymer material, holographic volume grating device and preparation method of holographic volume grating device

    CN115433313A